STUDENTS’ PERCEPTION TOWARD AMERICAN AND BRITISH ENGLISH IN COKROAMINOTO UNIVERSITY - Hermini Hermini (Institut Agama Islam Negeri Palopo, 2019)
This research aims to find out (1). Variety of English that the students use most in Cokroaminoto University of Palopo (2). The students’ perceptions toward American and British English. It is a descriptive research. The population of this research is the seventh students of Cokroaminoto Palopo which consists of three parallel classes. The total population is 120 students. Cluster random sampling technique is used to determine the sample. This research took one class as sample. The result of this research shows the students use American English variety in vocabulary even though they think that they mix both varieties of English and they have ever exposed both of varieties, the students prefer American English in teaching learning process as they think that it easy to be pronounced and understood and it is frequently used by them. Other result shows that the students mostly notice the differences between American and British English on pronunciation. But minority of the students still think that British English is cool, more formal, general variety of English and they like it.